The Bajratari case: are all resources good enough for EU law? - Benedita Menezes Queiroz (Market and Competition Law Review)
The Bajratari case is a significant contribution of the Court of Justice of the European Union to the clarification of the meaning of the condition of sufficient resources within the regime of the Citizens Directive 2004/38 (Article 7 (1) (b)). Moreover, it is also a step towards strengthening EU citizen’s right to move and reside in another Member State. In this decision the Court held that income that results from the exercise of professional activities without a lawful residence and employment permit is not to be excluded from the condition of sufficient resources imposed by EU law to a Union citizen who is residing for more than three months in another Member State.